Isolation And Screening Of Fungal Species For Decolourization Of Textile Dyeing Mill Effluent - Bhagat, Tejashree N.; Pawar, Asmita C.; Pathade, Aparna G.; Pathade, Girish R. (Journal of Neonatal Surgery, 2025)
Textile wastes are coloured, highly alkaline, high in BOD and suspended solids and high in temperature. A dye is a substance used to impart colour to fabrics, food and other objects of beautification. Synthetic dyes are used extensively for textile dyeing. Colour is the contaminant to be detected and even small amounts of dyes as low as 5ppm for reactive dyes are clearly visible. These dyes are highly resistant to microbial degradation and hence wastes containing them are less amenable to treatment as far as decolourization is concerned. So, attempts are made to isolate and screen out mold species for decolourization, and this waste can be safely disposed off in natural water bodies. The isolate showing considerable decolourization and reduction in BOD is Aspergillus spp. Testing of its efficiency with individual textile dyes, textile waste and optimization conditions these off is in pipeline.